The East African contribution to the formalisation of the soil catena concept - Borden, R. Wayne; Baillie, Ian C.; Hallett, Stephen H. (Elsevier, 2019)
The concept of the soil catena was first explicitly formalised by Geoffrey Milne and his colleagues in East Africa in the 1930s. It has been widely adopted and applied in soil survey and continues to be of great value in soil and other field sciences The concept characterises widespread patterns in which distinctive associations of soils and vegetation are consistently located in specific slope positions. The formalisation of the concept in an area well outside the mainstream of soil research appears to have been due to the combination of highly visible recurrent patterns of red slope soils overlooking dark valley clays in East Africa’s extensive savannahs, together with a group of receptive and collaborative soil scientists working in a supportive institutional environment. The concept is often attributed to Geoffrey Milne, the group’s coordinator, but we show that several colleagues and friends also contributed. We summarise some of the early soil catenas characterised by Milne and his colleagues in Uganda, Kenya and Tanganyika Territory (now Tanzania). Even at the beginning, it was appreciated that the catena was not universally applicable and that heterogeneity of parent materials can override catenary patterns. The catena was quickly and widely adopted in soil science, and this diffusion has led to some broadening of the definition, and several types of soil pattern are now designated as catenas. The concept has also spread beyond soil science and is used by ecologists, geomorphologists and hydrologists amongst others. It continues to be a paradigm of great explicative and educational power in soil science and ecology.
Keywords: Geoffrey Milne; Toposequence; Kenya; Tanzania; Uganda